The library, the digital and the quest for open access - Gouveia, Luis Borges (2013)
The growing number of information sources combined with available digital content and the widespread of computers and networks are putting pressure on how libraries organize and compete with such a new, brave (and savage) world. Facing new demands from society, and taking the university libraries context, a number of issues are introduced for discussion as the case of digital libraries and open access regarding its impact for both authors and publishers.